(untitled) (Global Journal of Medical Research, 2020)
The wrath of the COVID-19 pandemic has crippled the entire world in a state of a medical emergency. The number of cases has been increasing at an alarming and exponential rate and exhausting the medical resources vastly, at the same time questioning the future of such a deadly pandemic. An amalgamation of medical and non-medical knowledge is being followed globally to flatten the curve. However, without any proven cure at hand, several drugs are being researched into studies like Favipiravir, Remdesivir, Tocilizumab, Hydroxychloroquine, to gain substantial evidence of their use either individually or in combination, supplemented by supportive therapy, vitamins, and zinc, to effectively treat the patients and curb the mortality rate of the population.